Ferrous sulfate liquid for the treatment of iron deficiency anemia - Soemantri Soemantri; A. G. Soedigbia; I. Hardiman; Taty Hendarto; Widjaja Widjaja (Paediatrica Indonesiana, 1981)
A study on the effect of ferrous sulfate liquid (lberet - 500 liquid) was conducted on a group of well-nourished children aged 6 months - 5 years.After 3 months 0/ treatment, hematological measurements revealed a statistically significant improvement as compared to the control group receiving placebo. Side effects were also found to be minimal. Thus ferrous sulfate liquid is recommended for treatment or supplement to anemia eradication, preferably associated with a high dose of vitamin C.